Perancangan dan Implementasi Aplikasi Bank Sampah untuk Penjadwalan Pengangkutan dan Transaksi Sampah Menggunakan Metode Extreme Programming - Inzani, Febrilia Putri; Adi, Taufik Nur; Thohiroh, Elvira Lailatuth (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
A waste bank is a facility that functions to manage waste by applying the principles of 3R (Reduce, Reuse, Recycle) to support sustainable environmental programs and provide economic benefits to the community. Bank Sampah Capetang, located in Kelurahan Sekejati, Kecamatan Buah Batu, Kota Bandung, faces several operational management issues, particularly in transaction recording and waste transportation scheduling, which are often missed. These issues impact daily operational uncertainty and the potential loss of important data. This study aims to provide a solution by developing a web-based information system that integrates waste transportation scheduling and transaction recording, as well as providing a unified platform for Bank Pusat and Bank Unit managers to operate the waste bank. The system was developed using the Extreme Programming (XP) method, known for its iterative approach in software development. The technologies implemented in this system include the use of Unified Modeling Language (UML) for system modeling, the Laravel framework for application development, MySQL for database management, as well as Black Box Testing and User Acceptance Testing (UAT) for application testing. The testing results show that most tests were successful (